Transnational Entrepreneurship in South East Asia Japanese Self-Initiated Expatriate Entrepreneurs - Yokoyama, Kazuko; Birchley, Sarah Louisa (Emerging-Economy State and International Policy Studies,, 2020)
This open access book brings together narratives of inbound and outbound expatriate entrepreneurship in Japan to provide a comprehensive overview of international entrepreneurship in the region. Through in-depth interviews with expatriate entrepreneurs, policymakers, and additional stakeholders it provides the reader with a solid understanding of the current landscape of international entrepreneurship as it relates to Japan and the challenges for policymakers. The topics addressed in this book include definitions of expatriate entrepreneurship, entrepreneurship policy development and implementation, concepts of mindset, cultural brokerage, community, and identity as they relate to Japanese self-initiated expatriate entrepreneurs working in South East Asia and to non-Japanese self-initiated expatriate entrepreneurs working in Japan. Additionally, the book provides an overview of issues connected to regional development and economic growth in Asia. Illustrated through carefully chosen cases from Japan, Myanmar, Thailand, Cambodia, Vietnam, and Indonesia and developed by connecting these cases to policy and interdisciplinary studies, this book is highly recommended to scholars, policymakers and practitioners who seek an in-depth and up-to-date integrated overview of the field of expatriate entrepreneurship in Asia. .